2011
DOI: 10.4021/wjon362w
|View full text |Cite
|
Sign up to set email alerts
|

The Management Dilemma of Leiomyosarcoma of the Ovary

Abstract: Ovarian leiomyosarcomas (OLS) have a poor prognosis due to their late presentation and aggressive nature. This case illustrates that surgery alone can offer disease free survival in cases of early stage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 2 publications
1
34
1
3
Order By: Relevance
“…Wildlife is facing serious challenges all over the world, and many fauna and flora species are continuously driven closer to extinction on a daily basis (Ijeomah et al 2013). According to Goodall (2011), Poaching and illegal trade in wildlife has become an organized, lucrative and a capital intensive business, with trafficking routes extending from remote national parks and reserves, where animals are trapped and killed, to major urban centres where they are sold and consumed.…”
Section: Introductionmentioning
confidence: 99%
“…Wildlife is facing serious challenges all over the world, and many fauna and flora species are continuously driven closer to extinction on a daily basis (Ijeomah et al 2013). According to Goodall (2011), Poaching and illegal trade in wildlife has become an organized, lucrative and a capital intensive business, with trafficking routes extending from remote national parks and reserves, where animals are trapped and killed, to major urban centres where they are sold and consumed.…”
Section: Introductionmentioning
confidence: 99%
“…E J Goodall et al presented a case of ovarian leiomyosarcoma with reported disease-free survival of 22 months after surgery alone [3]. In a 58-year-old postmenopausal woman with Stage Ia leiomyosarcoma of ovary, Zygouris et al reported no evidence of recurrence 21 months after initial surgery, without any postoperative adjuvant therapy [6].…”
Section: Discussionmentioning
confidence: 99%
“…On gross examination, these tumors are found to be similar to any other sarcomas. Controversy exists in the management of leiomyosarcoma of ovary with no established treatment for these tumors other than surgery [3]. Debulking surgery, consisting of total abdominal hysterectomy, bilateral salpingo-oophorectomy, and removal of the tumor masses, is the recommended surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kurian et al (4) treatment of choice is radical surgery followed by adjuvant chemotherapy or radiotherapy. Although the overall prognosis is poor, early stage disease treated with optimal surgery may offer significant improvements in survival (11) .…”
Section: Discussionmentioning
confidence: 99%